Applying Communicative Language Teaching in Teaching English for Foreign language Learners. - Laili, Manalul (Ahmad Dahlan Journal of English Studies, 2015)
AbstractTeaching second or foreign language is not easy. Many researchers believe that the teachers should know several methods and teaching strategies in teaching language; such as, communicative language teaching, the grammar-translation method, the direct method, the audio-lingual method, the silent way, the suggestopedia, communicative language learning, total physical response, natural approach, and many more. In early 1980s, many educators assumed that communicative approach is a better way to teach second language to the students and this approach incorporated into the classroom (Brown, 2001). This essay will explore what communicative language teaching is and describe the factors led to its emergence in English language teaching.